Existence of Pusat Kegiatan Belajar Masyarakat (PKBM) in the Era of Society 5.0 - Hirzulloh, Muhammad Faiq (PKBM DAARUL AHKAAM, 2024)
This study aims to determine the existence of non-formal educational institutions Pusat Kegiatan Belajar Masyarakat (PKBM) in the era of society 5.0 as an educational institution whose role is very helpful in dealing with educational problems can be an alternative school/education, as well as a solution in meeting the needs of the community and children who drop out of school. This research was conducted with a qualitative approach using description. Data and information were collected using documentation, observation and interviews by respondents tutors and organizers at PKBM Daarul Ahkaam, then with data triangulation techniques researchers can conclude. Existence as an educational institution PKBM Daarul Ahkaam as an alternative in solving educational solutions, especially for people who have not completed education in the current era of society 5.0. The existence of concern from tutors and organizers at PKBM Daarul Ahkaam with the existence of dropout handling officers, this is very useful for the community in general because it can be a solution to educational problems, with the existence of equivalency education programs (Package A / SD, Package B / SMP and Package C / SMA) so that it can help the community to complete their current education.